DOES KNOWLEDGE AND INCREASED AWARENESS AMONG OUR FEMALE POSTGRADUATE MEDICAL STUDENTS CONTRIBUTE TO IMPROVE THEIR HEMOGLOBIN LEVELS? - Mary Sam, Sancy; Udaykumar, Padmaja (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Anemia is frequent among young women including medical students that remain unnoticed. This study was conducted to determine the prevalence of anemia in women postgraduate (PG) medics. Methods: Hemoglobin (Hb) level of the participants was estimated and correlated with history. Results: Eligible women PG medics (n=100) with a mean±standard deviation (SD) age of 25.92±1.5 years and body mass index (BMI) of 21.51±2.97 were enrolled. Of 44 anemic students, 32 had moderate anemia and 21 (47.73%) belonged to the 3rd year postgraduation. Only 16 students were underweight, eight in anemic and non-anemic group each. None had any history of occult bleeding. Twenty-four (24.0%) students had taken anti-helminthic treatment within 6 months before enrollment. Mean Hb levels were 11.54±1.21 g/dL. There was a statistically significant difference (p<0.05) between mean Hb level of the anemic students (Hb - 10.35 g/dL) and the non-anemic individuals (Hb 12.49 g/dL). There was no statistical significant difference (p>0.05) in the occurrence of anemia among vegetarians (mean±SD Hb 11.21±1.11 g/dL) and non-vegetarians (mean±SD Hb 11.61±1.23 g/dL). There was no statistical significance (p>0.05) in Hb level/anemia and BMI, dietary habits, duration, and heavy flow during menstruation between non-anemic and anemic students. Conclusion: Anemia is still a concern in young women, and PG medical students are no exempt. Although none had severe form, anemia of moderate severity is prevalent among our PG students. Dietary habits did not influence or contribute to the maintenance of adequate Hb levels. Knowledge increased awareness and being self-sufficient did not contribute to maintain adequate Hb level.